2019
DOI: 10.1002/acm2.12744
|View full text |Cite
|
Sign up to set email alerts
|

Two‐dimensional solid‐state array detectors: A technique for in vivo dose verification in a variable effective area

Abstract: Purpose:We introduce a technique that employs a 2D detector in transmission mode (TM) to verify dose maps at a depth of d max in Solid Water. TM measurements, when taken at a different surface-to-detector distance (SDD), allow for the area at d max (in which the dose map is calculated) to be adjusted. Methods:We considered the detector prototype "MP512" (an array of 512 diodesensitive volumes, 2 mm spatial resolution). Measurements in transmission mode were taken at SDDs in the range from 0.3 to 24 cm. Dose mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Further experiments will be performed on different topologies of the grating structure, including much thinner gratings. It has been shown that the electron contamination reduces with distance from the linac head [25], [26], hence in the future we will include studies at different SSDs. The trench dimensions and overall thickness of the grating will be optimized to minimize the contribution from contamination electrons to the modulation total signal, allowing the photon signal to be extracted.…”
Section: Discussionmentioning
confidence: 99%
“…Further experiments will be performed on different topologies of the grating structure, including much thinner gratings. It has been shown that the electron contamination reduces with distance from the linac head [25], [26], hence in the future we will include studies at different SSDs. The trench dimensions and overall thickness of the grating will be optimized to minimize the contribution from contamination electrons to the modulation total signal, allowing the photon signal to be extracted.…”
Section: Discussionmentioning
confidence: 99%
“…Different layouts were explored (Stansook et The Magic Plate, the Duo and the Octa were used for dosimetry in FFF beams (Biasi et al 2018c), for dosimetry in a CyberKnife ® (Accuray) (Biasi et al 2018b), and in transmission mode to verify dose maps at a depth of maximum dose (d max ) in Solid Water (Utitsarn et al 2019b). They were also used in combination with a movable platform, using a patient-specific 3D (x, y, time) lung-motion pattern and the electromagnetic beacon motion tracking system (Petasecca et al 2015b), and to measure dose maps during In synchrotron-based MRT (Bartzsch et al 2020), the FWHM of the micro-beams is one of the parameters used to assess the quality of the radiation field.…”
Section: Monolithic Arrays Of Diodes and Strip Detectorsmentioning
confidence: 99%